Nucleic acid-loaded lipid-polymer nanohybrids as novel nanotherapeutics in anticancer therapy. (2nd June 2020) - Rahman, Mahfoozur; Alharbi, Khalid S.; Alruwaili, Nabil K.; Anfinan, Nisrin; Almalki, Waleed H.; Padhy, Ipsa; Sambamoorthy, Unnam; Swain, Suryakanta; Beg, Sarwar
ABSTRACT: Introduction: Since decades, cancer is a major public health problem worldwide. The increasing knowledge of molecular and tumor biology has significantly changed the cancer treatment paradigms during the past few years. Area covered: Conventionally, the first-line treatment of solid tumors is their surgical removal followed by chemotherapy and/or radiation treatment. Unfortunately, these approaches often fail, and the patient may discontinue the treatment before the complete eradication of tumors due to therapeutic and toxicological limitations. In this regard, the nucleic acid-based treatment therapy has been widely used in the management of cancer. However, nucleic acid delivery to the target sites is highly challenging because of their molecular size, difficulties to pass cellular membranes, and susceptibility toward enzymatic and/or chemical degradation. Expert opinion: Researchers have now overcome many problems associated with delivering nucleic acids to the target tissues by preventing them from off-target side effects and overcoming rapid degradation and clearance in the bloodstream using the lipid–polymer hybrid nanoparticles (LPHNs). The present review, therefore, aims to provide an overview account on LPNHs, their preparation, characterization, application with special emphasis on intracellular delivery/transfection of nucleic acids in the management of cancer, and key aspects of challenges in its delivery and clinical transition.